Penile Metastases presenting as priapism in Carcinoma Prostate -A Case Report and review of literature - Gupta, Sweety; Singh, Dinesh; Agarwal, Sandeep; De, Sudarsan (Asian Journal of Medical Sciences, 2013)
Metastatic neoplasms of the penis are uncommon. The most common primary organs have been reported to be the bladder and prostate. In the present report, a patient with priapism was demonstrated to have carcinoma prostate complicated with penile, lung, and liver metastasis in the absence of bone involvement and normal serum PSA levels. DOI: http://dx.doi.org/10.3126/ajms.v4i2.7827 Asian Journal of Medical Sciences 4(2013) 51-54